2023
DOI: 10.32604/cmc.2023.034082
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of DVR and D-STATCOM in Presence of Wind Energy System

Abstract: The present study suggests that series voltage injection is more effective than parallel current injection to improve voltage quality on the load side. The line voltage can be accurately symmetrized at the connection point by creating and controlling a series voltage component in each phase. This is more reliable and effective than parallel current injection. A dynamic voltage restorer (DVR) and a distribution static synchronous compensator (DSTAT-COM) were utilized to provide the required power. The DVR is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In the literature it is shown that DSTATCOM can protect the network against drops, surges, voltage fluctuations, current harmonics and bad power factor [1][2][3][4][5][6][7][8]. The above-mentioned consequences are those which evidently result from the occurrence of single-phase, two-phase and or three-phase short circuits on the distribution networks.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature it is shown that DSTATCOM can protect the network against drops, surges, voltage fluctuations, current harmonics and bad power factor [1][2][3][4][5][6][7][8]. The above-mentioned consequences are those which evidently result from the occurrence of single-phase, two-phase and or three-phase short circuits on the distribution networks.…”
Section: Introductionmentioning
confidence: 99%